Vascular leakage in dengue – clinical spectrum and influence of parenteral fluid therapy. Issue 3 (3rd February 2016) - Rosenberger, Kerstin D.; Lum, Lucy; Alexander, Neal; Junghanss, Thomas; Wills, Bridget; Jaenisch, Thomas; ,
Abstract: Objective: Clinical management of dengue relies on careful monitoring of fluid balance combined with judicious intravenous (IV) fluid therapy. However, in patients with significant vascular leakage, IV fluids may aggravate serosal fluid accumulation and result in respiratory distress. Methods: Trained physicians followed suspected dengue cases prospectively at seven hospitals across Asia and Latin America, using a comprehensive case report form that included daily clinical assessment and detailed documentation of parenteral fluid therapy. Applying Cox regression, we evaluated risk factors for the development of shock or respiratory distress with fluid accumulation. Results: Most confirmed dengue patients (1524/1734, 88%) never experienced dengue shock syndrome (DSS). Among those with DSS, 176/210 (84%) had fluid accumulation, and in the majority (83%), this was detectable clinically. Among all cases with clinically detectable fluid accumulation, 179/447 (40%) were diagnosed with shock or respiratory distress. The risk for respiratory distress with fluid accumulation increased significantly as the infused volume over the preceding 24 h increased (hazard ratio 1.18 per 10 ml/kg increase; P < 0.001). Longer duration of IV therapy, use of a fluid bolus in the preceding 24 h, female gender and poor nutrition also constituted independent risk factors. Conclusions: Shock and respiratory distress are relatively rare manifestations of dengue, but some evidence of fluid accumulation is seen in around 50% of cases. IV fluids play a crucial role in management, but they must be administered with caution. Clinically and/or radiologically detectable fluid accumulations have potential as intermediate severity endpoints for therapeutic intervention trials and/or pathogenesis studies.